2017
DOI: 10.4103/ejd.ejd_264_16
|View full text |Cite
|
Sign up to set email alerts
|

A case of tooth fracture occurred upon medicating bisphosphonate for an elderly person: Preservation therapy and responses for Stage 0 of bisphosphonate-related osteonecrosis of jaw

Abstract: This case report aimed to report the progress of preservation therapy and response of symptoms and signs for Stage 0 of bisphosphonate-related osteonecrosis of jaw (BRONJ). A 68-year-old female was recognized having a tooth at the left upper first molar fracture upon medicating bisphosphonate (BP) in 2007. At that time, the extraction of the tooth was an absolute contraindication. Therefore, we performed preservation therapy. We observed the symptoms and signs every month. After 5 months, swelling and redness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…3,4 The first case of BRONJ was reported in 2003 by Marx, 5 and since then numerous cases have been reported in the literature. [6][7][8][9][10] BRONJ is a very serious condition that negatively impacts quality of life, producing a significant morbidity. 3,4,11 It is characterized by an area of exposed bone that presents for more than 8 weeks with no history radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The first case of BRONJ was reported in 2003 by Marx, 5 and since then numerous cases have been reported in the literature. [6][7][8][9][10] BRONJ is a very serious condition that negatively impacts quality of life, producing a significant morbidity. 3,4,11 It is characterized by an area of exposed bone that presents for more than 8 weeks with no history radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that BP causes the inhibition of osteoclasts, resulting in the reduction of bone resorption and bone remodelling, which leads to osteonecrosis of the jaw (ONJ), later known as BPrelated osteonecrosis of the jaw (BRONJ) [5,6]. It was first reported in 2003 by Marx [7], and subsequent cases have been extensively reported in the scientific literature, leaving a significant impact on quality of life and substantial morbidity [8][9][10][11][12]. It appears as a bone exposed for eight weeks or more without any history of radiation therapy [4,13].…”
Section: Introductionmentioning
confidence: 99%